The American pageant : a history of the republic - Bailey, Thomas Andrew, 1902-1983.; Kennedy, David M. (Lexington, Mass. : Heath, 1987)
Traces the history of the United States from the arrival of first Indian people to the present day.
Maps on lining papers.
Includes bibliographies and index.
Keywords: United States -- History; United States -- History